Ewald summation of electrostatic multipole interactions up to the quadrupolar level - Aguado, A; Madden, P (2003)
Ewald expressions were derived for the infinite lattice sums of electrostatic multipolar interactions, up to the quadrupolar level. The Ewald expressions for charge-quadrupole, dipole-quadrupole, and quadrupole-quadrupole interactions were detailed. Ewald summations of charge-dipole and dipole-dipole interactions were rederived to provide a unified derivation of all multipolar contributions.